Therapeutic Horizons: Gut Microbiome, Neuroinflammation, and Epigenetics in Neuropsychiatric Disorders - Shabnam Nohesara; Hamid Mostafavi Abdolmaleky; Ahmad Pirani; Sam Thiagalingam (Cells, 2025)
Neuroinflammation is a hallmark of many neuropsychiatric disorders (NPD), which are among the leading causes of disability worldwide. Emerging evidence highlights the significant role of the gut microbiota (GM)–immune system–brain axis in neuroinflammation and the pathogenesis of NPD, primarily through epigenetic mechanisms. Gut microbes and their metabolites influence immune cell activity and brain function, thereby contributing to neuroinflammation and the development and progression of NPD. The enteric nervous system, the autonomic nervous system, neuroendocrine signaling, and the immune system all participate in bidirectional communication between the gut and the brain. Importantly, the interaction of each of these systems with the GM influences epigenetic pathways. Here, we first explore the intricate relationship among intestinal microbes, microbial metabolites, and immune cell activity, with a focus on epigenetic mechanisms involved in NPD pathogenesis. Next, we provide background information on the association between inflammation and epigenetic aberrations in the context of NPD. Additionally, we review emerging therapeutic strategies—such as prebiotics, probiotics, methyl-rich diets, ketogenic diet, and medications—that may modulate the GM–immune system–brain axis via epigenetic regulation for the prevention or treatment of NPD. Finally, we discuss the challenges and future directions in investigating the critical role of this axis in mental health.